MicroRNAs in human tongue squamous cell carcinoma: From pathogenesis to therapeutic implications. (April 2017) - Karatas, Omer Faruk; Oner, Muhammet; Abay, Alican; Diyapoglu, Ali
Highlights: TSCC is an aggressive cancer of oral cavity constituting 41% of all oral carcinomas. Differential expression of microRNAs contribution to TSCC pathogenesis. MicroRNAs are suggested as biomarkers for diagnosis and prognosis of TSCC. MicroRNAs are considered as promising candidates for novel therapies against TSCC. Abstract: Being one of the most aggressive cancers of oral cavity, tongue squamous cell carcinoma (TSCC) constitutes 41% of all oral carcinomas. Despite considerable improvements in multimodal diagnosis and treatment techniques, TSCC still remains to be one of the most lethal cancer types in the head and neck region. MicroRNAs are endogenously synthesized, small, non-coding RNAs, which are responsible for post-transcriptional regulation of mRNA expression. They are involved in regulation of almost all biological processes through their spatial and temporal expression. Their deregulation participates in pathogenesis of various diseases, including human TSCC, where they can act as potent oncogenes or tumor suppressors. Extensive microRNA profiling in TSCC samples and further in vitro and in vivo functional characterization of differentially expressed microRNAs revealed their contribution to the underlying molecular mechanisms of TSCC initiation, development, progression, metastasis, chemo-radioresistance, and recurrence. They are suggested as diagnostic and prognostic biomarkers for TSCC due to their differential expression in tumor tissues and their stability in body fluids like plasma, oral cytology, and saliva. MicroRNAs are, therefore, considered amongst the most promising candidates for development of novel therapeutic approaches against TSCC. In this review, we summarized important findings including our own works on microRNAs as implicated in TSCC and the new insights into the roles of microRNAs in squamous cell carcinoma of tongue.